Impact of Driving Behavior on Power Consumption of Electric Bus: A Case Study on Rama IX Bridge - Lwin Yamon Phyo; Nattawoot Depaiwa; Masaki Yamakita; Burin Kerdsup; Manop Masomtob (2022 International Electrical Engineering Congress (iEECON), 2022)
Recently, the influence of the bus transportation system in Thailand has become the most critical impact on our surroundings. Government of Thailand has initiated the projects to replace internal combustion engine buses with net zero-emission. However, there are the problems of power consumption in battery electric buses, especially on climbing resistance which is a major impact on the power demand and recuperation. This paper aims to investigate the impact of driving behavior on power consumption of electric buses. Many scenarios have been created to study such behavior. Also, driving across Rama IX bridge which is the critical scenario on the performance of electric buses in Thailand has been evaluated.
Keywords: Advanced Battery Technologies Research; Electric Vehicles and Infrastructure; Electric and Hybrid Vehicle Technologies